The effect of different exercise training modes on improving quality of life in patients with Parkinson's disease: a network analysis - Li, Ying; Zhuang, Ruixin; Zhang, Jianhua; Liu, Xiaojie (Frontiers in Neurology, 2025)
ObjectiveReduced quality of life is a typical manifestation of Parkinson's disease (PD) patients, and exercise has a significant effect on improving the quality of life of PD patients. However, it is still unclear which exercise is effective in improving quality of life for people with Parkinson's disease. The aim of this study was to compare effective exercises for improving quality of life in patients with Parkinson's disease through a network meta-analysis.MethodWe conducted comprehensive database searches, including PubMed, Cochrane Library, Embase, Web of Science and CNKI. The included studies assessed methodological quality using the Cochrane Bias risk tool, and we collected information from the studies to compare the effects of 25 exercise interventions on quality of life in PD patients.ResultsThe results of the network meta-analysis showed that QG is higher than OE (MD, −9.26; 95%CI, −18.25 to −0.27), FAE (MD, −10.77; 95%CI −19.52 to −2.02), VR (MD, −10.65; 95%CI −19.70 to −1.60), TC (MD, −11.06; 95%CI −21.32 to −0.81), CT (MD, −11.42; 95%CI −20.73 to −2.11), RT (MD, −11.60; 95%CI −20.72 to −2.49), CE (MD −12.50; 95%CI −24.47 to −0.52), GT (MD −13.10; 95%CI −24.67 to −1.52) to better improve quality of life in patients with PD. DE is superior to TR (SMD, −2.10; 95%CI −3.75 to −0.45), BT (SMD, −2.63; 95%CI −4.93 to −0.32), BDJ (SMD, −4.14; 95%CI −6.15 to −2.14), RT (SMD, −4.54; 95%CI −6.94 to −2.14), TC (SMD, −5.28; 95%CI −7.73 to −2.84) in reduce depression. ROT is superior to TR (MD, 6.17; 95%CI 0.57 to 11.77), in improving balance capacity.ConclusionOur study found that QG improved the quality of life in patients with PD better than other forms of exercise. DE is more effective than other exercises in reducing depression in PD patients. ROT is better at improving the balance of PD patients.